Managing Risk for Development : International Risk Sharing - Aizenman, Joshua; Ötker-Robe, İnci (World Bank, Washington, DC, 2013)
This study reports that numerous direct and indirect international risk-sharing mechanisms exist, including (1) self-insurance at the state level, (2) market-based tools, (3) international labor mobility, (4) implicit hedges provided by macroeconomic flexibility, and (5) transfers and access to credit from international financial institutions (IFIs) and bilateral swap arrangements. While the various risk sharing tools help in dealing with exposure to tail risks and transitory shocks, a need exists for adjustment to permanent shocks. The World Bank and other international agencies have been engaged in dialogues concerning international community engagement, and in tangible resource transfers and managerial support of funds and projects aiming at ex-ante risk mitigation, and ex-post stabilization following economic or natural disasters. However, a too risk-averse attitude of the donor community may jeopardise the attempt to stabilize economies in transition, including those with fragile and conflict situations, and the proper heterogeneity of design of incentives and missions can help.